Answer:
(fog)(x) = 4x - 7
Step-by-step explanation:
f(x) = 2x-1 and g(x) = 2x-3;
(fog)(x) = f(g(x)
= f(2x - 3) = 2(2x - 3) - 1
= 4x - 6 - 1
= 4x - 7
Answer:
There is a similar problem with the same numbers except with no negatives so it goes 1 , 3 , 9 , 27, 81 for this question the answer is that it diverges.
Step-by-step explanation:
It was on the unit test review for edge and the answer was that it diverges.
Answer:
53.04
Step-by-step explanation:
Answer:
4x² -3y
Step-by-step explanation:
Answer:
14x
Step-by-step explanation:
please mark this answer as the brainlest